2004
DOI: 10.1096/fj.03-0372fje
|View full text |Cite
|
Sign up to set email alerts
|

Membrane cholesterol interferes with neuronal apoptosis induced by soluble oligomers but not fibrils of the amyloid‐β peptide

Abstract: Neuronal cell death in Alzheimer's disease (AD) is partly induced by the interaction of the amyloid-beta peptide (Abeta) with the plasma membrane of target cells. Accordingly, recent studies have suggested that cholesterol, an important component of membranes that controls their physical properties and functions, plays a critical role in neurodegenerative diseases. We report here that the enrichment of the neuronal plasma membrane with cholesterol protects cortical neurons from apoptosis induced by soluble oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
74
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 57 publications
14
74
0
1
Order By: Relevance
“…Very recently, Pillot and colleagues have also demonstrated that ASM was activated when rat cortical neurons were incubated with Aβ oligomers (Malaplate-Armand et al, 2006). The conflicting data with ASM and NSM implys that different molecular mechanisms and cellular targets may be involved in the neuronal apoptosis and cell death induced by soluble oligomers versus fibrillar Aβ (Sponne et al, 2004;White et al, 2005). These differences also may be due to the different cell types and culture conditions used.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Pillot and colleagues have also demonstrated that ASM was activated when rat cortical neurons were incubated with Aβ oligomers (Malaplate-Armand et al, 2006). The conflicting data with ASM and NSM implys that different molecular mechanisms and cellular targets may be involved in the neuronal apoptosis and cell death induced by soluble oligomers versus fibrillar Aβ (Sponne et al, 2004;White et al, 2005). These differences also may be due to the different cell types and culture conditions used.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence linking altered cholesterol levels in the brain with AD (for review, see Ref. 59) and the viability of A␤-treated neurons in culture (58). The EPR and structural data suggest that A␤M35V has an increased affinity for lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay as previously described (Pillot et al, 1999;Sponne et al, 2004). Cell nuclei were visualized using 4,6-diamidino-2-phenylindole (DAPI) staining (Sponne et al, 2004).…”
Section: Neuronal Viability and Monitoring Of Apoptosismentioning
confidence: 99%
“…Cell nuclei were visualized using 4,6-diamidino-2-phenylindole (DAPI) staining (Sponne et al, 2004). To evaluate the percentage of apoptotic cells, 10 independent fields of microscope were counted (approximately 400 cells) in 3 separate experiments with 3 determinations each (Kriem et al, 2005).…”
Section: Neuronal Viability and Monitoring Of Apoptosismentioning
confidence: 99%